Recycling Ash and Slag Waste from Thermal Power Plants to Produce Foamed Geopolymers - Elena A. Yatsenko; Boris M. Goltsman; Andrey I. Izvarin; Viktor M. Kurdashov; Victoria A. Smoliy; Anna V. Ryabova; Lyudmila V. Klimova (Energies, 2023)
Ash and slag waste (ASW) from coal combustion creates significant environmental and economic challenges. A promising method of ASW recycling is alkali activation with geopolymer material formation. This study investigates the influence of activating solution components (sodium hydroxide and sodium silicate) on the formation of porous geopolymers using ASW of different origins. The sodium hydroxide content of 0–4 wt.% and the sodium silicate content of 17–25 wt.% were studied. An increase in sodium hydroxide resulted in decreased density, but it adversely affected the strength. An increase in sodium silicate led to a compromised porous structure with relatively high density and compressive strength. An optimal composition, S19N3, comprising 3 wt.% of sodium hydroxide and 19 wt.% of sodium silicate obtained porous geopolymers with uniformly distributed 1.4–2 mm pores and a corresponding density of 335 kg/m3, a compressive strength of 0.55 MPa, a porosity value of 85.6%, and a thermal conductivity value of 0.075 W/(m·K). A mechanism for porous geopolymer formation was developed, including the interaction of alkaline components with ASW and a foaming agent, foaming, curing, and densification. The mechanism was examined using ASW from the Severodvinsk CHPP-1. This study allows for the optimization of geopolymer mixtures with various waste sources and the utilization of waste materials in the construction industry.